Schwann cell reprogramming and Esophageal squamous cell carcinoma: analysis of transcriptome data - Lima, Roberta Karolline de Souza; Rolim, Giovanna Barros; Soares, Érika de Fátima Machado; Lustosa Neto, Miguel Ferreira; Omena Neta, Genilda Castro de; Rocha, Rodger Marcel Lima; Oliveira, Tatiana Farias de; Fraga, Carlos Alberto de Carvalho (Acta Scientiarum. Biological Sciences, 2024)
Perineural invasion (PNI) occurs when cancer cells infiltrate nerves or the adjacent nervous tissue. The significance of PNI in Esophageal cancer remains controversial. Therefore, identifying new prognostic factors for Esophageal squamous cell carcinoma (ESCC) is important for optimizing treatment and improving outcomes. We investigated transcriptomic datasets and differentially expressed genes (DEGs) through meta-analysis and bioinformatics analysis. The set of core DEGs was subjected to functional and pathway enrichment analyses and integrated with genome-scale human biomolecular networks. We also analyzed how each gene was correlated with patient survival. Our findings indicate that the "cGMP-PKG signaling pathway" and "Cytokine-cytokine receptor interaction" pathways were deregulated in ESCC. These pathways play a role in the regeneration of Schwann cells and the progression of ESCC. Also, different expressions of NCAM1 and s100 genes suggest that Schwann cells are involved in this type of cancer’s PNI. Our results suggest that the tumor can induce the dedifferentiation of Schwann cells, which promotes detachment of cancer cells from the tumor, guiding them to the perineural tissue. This study’s results encourage further studies for clinical and experimental validation of the data found.